Giant days Volume 10 - Allison, John, 1976-; Allison, John, 1976- (Boom! Box, 2019)
Daisy, Esther, and Susan's last year at university is getting a bumpy start, with everything strange after Ed's declaration of love followed by grievous injury, Daisy with nowhere to live, and McGraw and Susan at odds over their new flat! The final year of university is about to start for best mates Daisy, Esther, and Susan, and everything is going completely off the rails. From finding somewhere to live at the last minute, to broken bones, to the looming terror of the adult world, this semester is one you won't want to miss. John Allison (Bad Machinery, Scary Go Round) and illustrators Max Sarin and Julia Madrigal are our "resident advisors" for this action-packed fall term, which collects Issues #37-40 of the Eisner Award-nominated series.